Spatial molecular profiling: platforms, applications and analysis tools. Issue 3 (6th August 2020) - Zhang, Minzhe; Sheffield, Thomas; Zhan, Xiaowei; Li, Qiwei; Yang, Donghan M; Wang, Yunguan; Wang, Shidan; Xie, Yang; Wang, Tao; Xiao, Guanghua
Abstract: Molecular profiling technologies, such as genome sequencing and proteomics, have transformed biomedical research, but most such technologies require tissue dissociation, which leads to loss of tissue morphology and spatial information. Recent developments in spatial molecular profiling technologies have enabled the comprehensive molecular characterization of cells while keeping their spatial and morphological contexts intact. Molecular profiling data generate deep characterizations of the genetic, transcriptional and proteomic events of cells, while tissue images capture the spatial locations, organizations and interactions of the cells together with their morphology features. These data, together with cell and tissue imaging data, provide unprecedented opportunities to study tissue heterogeneity and cell spatial organization. This review aims to provide an overview of these recent developments in spatial molecular profiling technologies and the corresponding computational methods developed for analyzing such data.